2011
DOI: 10.3109/10428194.2011.606382
|View full text |Cite
|
Sign up to set email alerts
|

Azacitidine in patients with acute myeloid leukemia medically unfit for or resistant to chemotherapy: a multicenter phase I/II study

Abstract: The safety and efficacy of azacitidine (5-day schedule) were assessed in a multicenter study in 40 patients (median age 72 years) with acute myeloid leukemia (AML) medically unfit for (n = 20) or resistant to chemotherapy (n = 20) from April to October 2008. Median marrow blasts were 42%. After a median follow-up of 13 months, response (complete remission [CR]/partial remission [PR]/hematologic improvement [HI]) was 50% and 10% in newly diagnosed and relapsed/refractory patients, respectively (p = 0.008). Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 29 publications
5
53
0
1
Order By: Relevance
“…The response rates and the overall survival observed in our study are in consonance to those reported by other groups [16,17,19,26]. It is noteworthy that the rates of CR obtained with AZA are equivalent to those obtained in some published series of elderly patients treated with IC [11].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The response rates and the overall survival observed in our study are in consonance to those reported by other groups [16,17,19,26]. It is noteworthy that the rates of CR obtained with AZA are equivalent to those obtained in some published series of elderly patients treated with IC [11].…”
Section: Discussionsupporting
confidence: 91%
“…In this setting it had proven to be well tolerated including by those more elderly [25]. Based on this experience, several groups have tested the efficacy and safety of AZA in elderly patients with AML with promising results [16,17,19,26].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are conflicting results as to whether, in this patients setting, the achievement of CR can actually have an impact on crude survival [13,14]. A superior OS has been demonstrated in AML patients with 20-30% bone marrow blasts treated with azacitidine compared to conventional treatment [13,14], while three recent studies [16,[29][30] showed a beneficial outcome in previously untreated AML patients, including patients with more than 30% bone marrow blasts, but a correlation with CR and survival remains unclear [13][14][15][16]. In our study, in accordance with the literature [16,22], the response rate seems to be correlated with PS (<2 vs ≥2) and karyotype (adverse vs intermediate) both in univariate and multivariate models (Tables 4 and 5), although the impact of the same variables on OS was confirmed at multivariate analysis only for ECOG ( Table 6).…”
Section: Discussionmentioning
confidence: 98%
“…Studies of 5-AZA in AML have shown CR rates in the range of 15% - 20% and median OS ranges of 19 to 24.5 months among patients with 20-30% bone marrow blasts and less proliferative disease. 89-94 Decitabine treatment in AML has also produced similar response rates ranging from 18% to 24% and a survival benefit in responding patients (7.7 to 14.4 months). 95,96 A randomized phase III study of decitabine vs. supportive care or LDAC demonstrated a significant OS benefit (7.7 vs. 5 months, p=0.37) and led to its approval by the European Medicines Agency for the treatment of AML in patients ≥ 65 years.…”
Section: Npm1 Mutated Amlmentioning
confidence: 94%